The study of groups - Klein, Josephine, 1926-2018 (International library of sociology. Sociology of behaviour and psychology, 1998)
In attempting to understand the psychological aspects of the developmental process and socialisation, the distinct disciplines of sociology and psychology were brought together for the first time. Titles in the Sociology of Behaviour and Psychology set of the International Library of Sociology analyse how behaviour is formed and learned.